Low Power and Lossy Networks Routing Improvement in IoT Applications - basil gazi, Osama; S.mohammed, Ghada (Journal of Madenat Alelem University College, 2024)
IoT has recently attracted the interest of engineering, educators, and governmental units from various enterprises. IoT poses additional risks, including flexibility, big data analytics, security, availability, connectivity, performance, and mobility. This study will concentrate on providing the most optimal routing amongst various network environments, including wired, wireless, and IoT sensors. The main challenges involved in designing a routing protocol, as well as the difficulties involved in the design of a routing protocol, are described in this book. The many classifications of routing protocols are also reviewed. The constraints of dynamic topology, node mobility, scalability, and restrictive bandwidth are the most frequent difficulties faced by the Internet of Things. The review covers a variety of routing protocols, including reactive, multipath, location-aware, hybrid multicast, Geo-cast, and power-aware protocols. The most popular routing protocols have been carefully studied, and discussions of routing techniques and analyses of the strengths and weaknesses of the existing research field are included. The analysis of current routing protocols is conducted based on the shortest path for the least transmission time. Finally, the research community and academic community examine the difficulties in routing that need to be addressed.